This or that questions about technology : you decide! - Bearce, Stephanie (North Mankato, Minnesota : Capstone Press, 2021)
Technology is advancing rapidly. Transportation experts think self-driving cars could fill the streets someday soon. Designers are experimenting with different artificial intelligence devices. The choices designers make now will affect our future. What choices would you make in a world of new technology? Would you rather take nanobot vitamins or use a wearable health monitor? Would you rather take to the skies with a jetpack or on a flying motorcycle? Would you rather have telescopic eyesight or supersonic hearing? It's your turn to pick this or that!
Includes bibliographical references (page 32).
4.6
3-6
690L
S
Keywords: Technology -- Miscellanea -- Juvenile literature; Technology -- Miscellanea; Technology -- Juvenile literature